Disproportionate confinement of African-American juvenile delinquents - Mooradian, John K., 1953- (Criminal justice (LFB Scholarly Publishing LLC), 2003)
Mooradian finds that the disproportionate number of African-American youth who are confined as juvenile delinquents is not purely a product of their delinquent acts. In analyses of real-world social agency data, particular combinations of personal, familial, societal, and juvenile-justice variables emerged as the best explanations for the problem. In addition, Mooradian suggests that culturally-sensitive measures are required in order to represent the particular experience of African-American youth and families. Analysis of some widely used clinical measures indicates that many of the included items and factors are inapplicable to African-Americans. Thus, he presents new scales, developed from these instruments, to improve the validity of measurement and the utility of the results. Historical issues in confinement of juveniles, and implications for further research, policy decisions, and intervention are discussed.